Modelling, imaging and measurement of distortion, drag and break-up of aircraft- icing droplets - Luxford, Geoffrey; Hammond, David W.; Ivey, Paul C. (Cranfield University, 2005)
The distortion, drag and break-up of supercooled drizzle droplets in aircraft icing was investigated in ambient conditions. An effective efficient computer procedure was developed for the distortion and drag of small droplets, < 1mm, at low Reynolds numbers, < 1000, and high Weber numbers, > 10. High-speed videos and photographs were obtained with an improved high-intensity LED strobe. Experimental measurements validated the drag model for droplets distorted by a rapidly accelerating airflow in a convergent wind tunnel. To prevent droplet coalescence, due to wake interactions, droplets were generated with a steady jet impinging of a rotating slotted disk.